Energy cost savings based on the UPS - Phu Tran Tin; Duy Hung Ha; Minh Tran; Quang Sy Vu (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Energy-saving, improving energy efficiency, and finding a new efficient way to use energy are considered as an urgent problem in over the world. In this paper, we consider the economics of energy use in combination with energy storage units where two forms of electricity exist in the power system. Then the problem of optimizing the installation capacity (to optimize the investment costs for energy storage) is presented and investigated in connection with the conversion systems. The topic opens a very significant result, including the introduction of a mathematical model to calculate the simulation in optimizing the installation capacity of the equipment in the system, multi-source power, as well as voltage and power stability benefits.